Advanced Materials and Technologies for Fuel Cells - Viviani, Massimo; Barbucci, Antonio; Carpanese, Maria Paola; Presto, Sabrina; Viviani, Massimo; Barbucci, Antonio; Carpanese, Maria Paola; Presto, Sabrina (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Fuel cells are expected to play a relevant role in the transition towards a sustainable-energy-driven world. Although this type of electrochemical system was discovered a long time ago, only in recent years has global energy awareness, together with newly developed materials and available technologies, made such key advances in relation to fuel cell potential and its deployment. It is now unquestionable that fuel cells are recognized, alongside their possibility to work in the reverse mode, as the hub of the new energy deal. Now the questions are, why are they not yet ready to be used, despite the strong economic support given from the society? What prevents them from being entered into the hydrogen energy scenario in which renewable sources will provide energy when it is not readily available? How much are researchers involved in this urgent step towards change? This book gives a clear answer, engaging with some of the open issues that explain the delay of fuel cell deployment and, at the same time, it opens a window that shows how wide and attractive the opportunities offered by this technology are. Papers collected here are not only specialist-oriented but also offer a clear landscape to curious readers and show how challenging the road to the future is.
English
Keywords: Research & information: general; Technology: general issues; polymer electrolyte fuel cell; cyclic current profile; transient behavior; pressure drop; Ohmic resistance; solid oxide fuel cells (SOFCs); ionic conductivity; Raman spectroscopy; powder X-ray diffraction; microbial fuel cell; low-cost ceramics; separator; membrane; porosity; pore size; water absorption; mercury intrusion; raman spectroscopy; powder x-ray diffraction; doped ceria; solid oxides fuel cells; Sm-doped ceria; high pressure X-ray powder diffraction; diamond anvil cell; equation of state; Rietveld refinement; SOFC; reliability; contamination; salt; oxygen starvation; concentration polarization; fuel cell application; microfluidic fuel cell; power supply; soft drinks; hydrogen production; alkaline water electrolysis; two-phases flow; CFD; two-phase process; BSCF; SOEC; rSOC; anodic overpotential; impedance spectroscopy; sealants; glass-ceramic; joining; CH4 internal reforming; solid oxide fuel cell; 2D local control; cell design optimization; active site degradation; tape casting process; open circuit voltage; activation energy; power density